Design requirements according to the formal integration in the design of interior spaces (Al-Academy, 2023)
The formal integration of the interior spaces in general and the commercial spaces of the watch shops in the large commercial centers in particular is the goal that the designers aim to reach in order for the interior space to become successful in terms of the design idea and its characteristics. Implementation mechanism. One of the reasons for achieving formal integration in the interior spaces of watch shops is the requirements of the design that must be available in these spaces to reach a state of formal integration between the interior and the exterior so that the space becomes fully integrated in all respects. Because of the aforementioned reasons for dealing with the research, through four chapters: The first chapter included the research plan and its problem, which was summarized in the following question: (What are the design requirements that must be available in the interior design? Shop spaces that sell watches as commercial spaces require formal integration)? The importance of the research, its objective, the objective limits, the spatial and temporal limits of the research were also highlighted, and the most important terms mentioned in the research title were identified. As for the second chapter, it included previous studies and the theoretical framework, which included two parts. The first dealt with formal integration into the interior spaces. As for the second, it dealt with the internal commercial spaces in all its details, in addition to the results of the theoretical framework in terms of indicators. As for the third chapter, it was devoted to the research procedures, as the researcher relied on the descriptive approach in analyzing the selected samples and models. The fourth chapter also included the results of the analysis and the conclusions obtained in light of the research objective, recommendations and proposals. and a list of sources and appendices.